PEMBANGKITAN TEGANGAN GENERATOR INDUKSI SATU FASA - Saleh Al Amin (Jurnal Ampere, 2018)
electric power generation machines currently used, induction generators arealternative electric energy generation machines that are being used, because they haveadvantages, especially in the field of construction which can reduce the manufacturing costs of engine manufacturing. At this time an induction generator is produced for one phase small power, which is mostly used for the household sector as a backup generator. Excitation of a single phase induction generator uses an exciter coil on the side of the rotor which is a closed loop circuit, and a coil at the side of the stator which is supplied with a capacitor. The voltage will be generated due to the magnetic remanence in the rotor core, which generates an induced voltage in the stator coil, so that the capacitor will be charged, which will eventually generate a nominal voltage on the side of the power coil at the stator. Dari beberapa mesin pembangkit tenaga listrik yang digunakan sekarang ini, generatorinduksi merupakan mesin pembangkit energi listrik alternatif yang mulai digunakan, karenamemiliki keunggulan, khususnya dibidang konstruksi yang dapat menurunkan biaya produksi pabrikasi mesin. Pada saat ini generator induksi diproduksi untuk daya kecil satu fasa, yang kebanyakan digunakan untuk sektor rumah tangga sebagai pembangkit cadangan. Eksitasi Generator induksi satu fasa menggunakan kumparan eksiter di sisi rotor yang merupakan rangkaian loop tertutup, dan sebuah kumparan di sisi stator yang diseri dengan kapasitor. Tegangan akan terbangkit karena adanya remanensi magnet di inti rotor, yang memnbangkitkan tegangan induksi di kumparan stator, sehingga kapasitor akan terisi muatan, yang akhirnya akan terbangkit tegangan yang nominal di sisi kumparan daya di stator